Post-transcriptional control of NLRP3 inflammasome activation in colonic macrophages - Filardy, Alessandra A. (Mucosal Immunol, 2015)
Colonic macrophages (cMPs) are important for intestinal homeostasis as they kill microbes yet produce regulatory cytokines. Activity of the NLRP3 inflammasome, a major sensor of stress and microorganisms that results in pro-inflammatory cytokine production and cell death must be tightly controlled in the intestine. We demonstrate that resident cMPs are hyporesponsive to NLRP3 inflammasome activation due to a remarkable level of post-transcriptional control of NLRP3 and proIL-1β protein expression, which was also seen for TNF-α and IL-6, but lost during experimental colitis. Resident cMPs rapidly degraded NLRP3 and proIL-1β proteins by the ubiquitin/proteasome system. Finally, blocking IL-10R-signaling in vivo enhanced NLRP3 and proIL-1β protein, but not mRNA levels in resident cMPs implicating a role for IL-10 in environmental conditioning of cMPs. These data are the first to show dramatic post-transcriptional control of inflammatory cytokine production by a relevant tissue-derived macrophage population and proteasomal degradation of proIL-1β and NLRP3 as a mechanism to control inflammasome activation; findings which have broad implications for our understanding of intestinal and systemic inflammatory diseases.